The Burden of Debt - Lerner, Abba P. (The Review of Economics and Statistics, 1961)
M /[ESSRS. Bowen, Davis, and Kopf have shown 1 that real burden of a project using up resources in can be shifted to generations by internal borrowing, providing one defines in a particular way. It just as easy to prove that all politicians are economists or that all economists are dunces, provided one defines economist in a particular way. But even if I call tail of a sheep a leg that will not turn sheep into quintapeds. The issue of course terminological rather than substantive. It nevertheless one of utmost importance because conclusion reached by Bowen et al., although not incorrect on their own definitions, bound to be misinterpreted as meaning what it seems to be saying in English and as indeed implying that most politicians understand economics better than economists most, if not all, of whom are dunces. Bowen, Davis, and Kopf are right when they agree that there absolutely nothing wrong with standard argument of modern economists that real burden of a debt can not be shifted to generations if it defined as the total amount of private consumption goods given up by community at moment of time borrowed funds are spent. But President Eisenhower appears convinced that costs of debt-financed public projects can be passed on to generations. Like Rabbi in story, Bowen et al. want to say that he too right, but in their enthusiasm they even say that purpose of their note is to suggest that in instance it President who -in at least one highly important sense right,' 2 thus clearly implying that economists are wrong. To make President appear right, Bowen et al. redefine present generation to mean people who lend money to finance project, and they redefine future generation to mean people who pay taxes that are used to repay principal and interest on loans. The perversity of redefinitions obscured by supposing that lenders (this generation), are all 2I years old at time of execution of project when they lend money and by supposing that they are repaid 44 years later, on their 6sth birthday, with funds obtained at that time from 2Iyear-old taxpayers (the next generation). The burden thereby shifted from this generation' to the next generation. What has been proved, if we obstinately insist in expressing conclusion in English, that it possible to shift burden from Lenders to Taxpayers or, we might say, fromn Lowells to Thomases. The Lowells are better off and Thomases are worse off than if Lowells had been taxed to raise money for project in first place. The red herring nature of having Lowells lend money now (so that we can call them generation) and having Thomases pay taxes in (so that they can be called generation) jumps to eye if we note that shifting of real burden of project from Lowells to Thomases (or indeed of any other burden) could take place just as well at time of project (or at any other time) by simply taxing Thomases instead of Lowells. No economist, so far as I am aware, has ever denied possibility of borrowing or of lending or of taxing some people instead of others, or of any combinations of such oper-